Conditions and procedures for in-hospital extracorporeal life support (ECLS) in cardiopulmonary resuscitation (CPR) of adult patients. (April 2016) - Swol, Justyna; Belohlávek, Jan; Haft, Jonathan W.; Ichiba, Shingo; Lorusso, Roberto; Peek, Giles J.
The use of extracorporeal life support (ECLS) in cardiopulmonary resuscitation (CPR; ECPR) has been repeatedly published as non-randomized studies, mainly case series and case reports. The aim of this article is to support physicians, perfusionists, nurses and extracorporeal membrane oxygenation (ECMO) specialists who regularly perform ECPR or are willing to start an ECPR program by establishing standards for safe and efficient ECPR procedures. This article represents the experience and recommendations of physicians who provide ECPR routinely. Based on its survival and outcome rates, ECPR can be considered when determining the optimal treatment of patients who require CPR. The successful performance of ECLS cannulation during CPR is a life-saving measure and has been associated with improved outcome (including neurological outcome) after CPR. We summarize the general structure of an ECLS team and describe the cannulation procedure and the approaches for post-resuscitation care. The differences in hospital organizations and their regulations may result in variations of this model.